Notes on Bricelochlorops Paganelli 2002 (Diptera: Chloropidae), with the description of a new species - Riccardi, Paula Raile (Zootaxa, 2016)
Bricelochlorops is a peculiar genus of Chloropinae because its species possess a swollen pedicel and an enlarged clypeus separated into two parts. According to previous phylogenetic studies, Bricelochlorops is known as the sister group of Psilochlorops and their relationships with the remaining chloropine genera are unclear (Paganelli, 2002; Riccardi & Amorim, 2012). There are two described species of Bricelochlorops, B. peregrinus Paganelli 2002 and B. celutae Carvalho-Filho & Esposito 2010. Both species are from Brazil and they are known only from the holotypes. Here, a further species from Peru is described, expanding the distribution of Bricelochlorops.